Multi-objective optimization models for urban readjustment in Turkey - Mehmet Kucukmehmetoglu; Abdurrahman Geymen (European Regional Science Association (ERSA), 2015)
The Dough Rule, in Turkish Land Law terminology, is a technical approach to readjust land resources in urban and agricultural areas. The Regulation on the 18th Article of the Land and Building Development Law defines the procedures of land readjustment. The procedure is as follows: First obtain cadastral land resources and ownership records and then overlay graphic information on top of zoning plans, later allocate the land resources to the relevant owners after proportional deduction for public uses, such as schools, roads, and parks. In many cases, in the allocation process, relevant parties compete for higher-value urban lots, and the resulting allocation scheme is taken to court. In this study, the primary goal is to develop techniques to handle the difficulties in land readjustment and reallocation practices in Turkey. The developed techniques contain three authentic features: The first feature is the original mathematical models based on operation research techniques. In this feature, there are two Linear Programing (LP) and one Mixed Integer Programming (MIP) models reallocating cadastral parcel areas into standard high quality urban subdivision lot(s) after proportional deduction of public land uses from all landowners under the frame of the Regulation on the 18th Article. The second feature is the evaluation criteria which are developed to present superiority of the optimization models over the existing expert based subjective practices in land reallocation. Those criteria are defined in the form of equations utilizing the allocation results (objective and subjective). The third feature is the graphical presentation of allocation results in a system of rays from cadastral parcel centroids to urban subdivision lot centroids. This provides a succinct way of visual comparison among alternative allocation results. Over a case study area, first, the optimization techniques are applied, then, the obtained results are evaluated via the evaluation criteria, and later visually presented by the ray based allocation/transfer diagrams. Finally superiority of the developed techniques are discussed for further sophistications.
Keywords: R52; 330; Q15 Land Ownership and Tenure - Land Reform - Land Use - Irrigation - Agricultur